1989
DOI: 10.1017/s0033822200012406
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Uptake in Aquatic Plants Deduced From Their Natural 13C and 14C Content

Abstract: ABSTRACT. 613C and 14C activity measurements were made on terrestrial, marsh and aquatic plants growing in their natural habitat of the Plitvice Lakes in northwest Yugoslavia. &3C values were ca -47%o for aquatic mosses, which indicate that the carbon source was dissolved inorganic carbon (DIC) from alkaline karst waters, following a C3 pathway, and ca -25%o for marsh plants, indicating the carbon source was atmospheric CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 18 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…To reduce the likelihood of contamination by older carbon we preferred to use organic material reflecting atmospheric 14 C concentrations, such as seeds and fruits from terrestrial plants (e.g. Marcenko et al, 1989;Törnqvist et al, 1992). Pollen analysis and radiocarbon dating was performed on the same sediment cores, preferably also in combination with sedimentological analysis (compare Dambeck, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the likelihood of contamination by older carbon we preferred to use organic material reflecting atmospheric 14 C concentrations, such as seeds and fruits from terrestrial plants (e.g. Marcenko et al, 1989;Törnqvist et al, 1992). Pollen analysis and radiocarbon dating was performed on the same sediment cores, preferably also in combination with sedimentological analysis (compare Dambeck, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Sample code no. HB1 HB3 HB4 GRC1 HB5 HB7 HB11 GRC2 GRC3 HB12 GRC4 IR1 Sample size 50 ml 50 ml 350 ml 0.5 kg 350 ml 50 ml 135 ml 0.1 kg 0.5 kg 500 ml V2 kg 200 ml Radiocarbon dates from bulk material or seeds and fruits from (semi-) aquatic plants, however, can reveal 14 C ages which are too old due to a 'hard water e¡ect' (Marcenko et al, 1989;To « rnqvist et al, 1992). Therefore, some of the Sourlie radiocarbon samples may have revealed 14 C ages that are too old.…”
Section: Radiocarbon Analysismentioning
confidence: 99%
“…1B). Marcenko et al (1989) showed that submerged aquatic plants take CO2 Table 4 However, recent true aquatic plants collected before the bomb-test period can be used for Ao determination. The 14C activity of moss (Cratoneurum comrnutatum) (Z-857, Table 2) collected at Plitvice Lakes around 1920 and stored in the Zagreb Botanical Garden Museum, agrees very well with Ao calculated by using other methods described in this paper.…”
Section: Dating the Organic Component Of Sedimentmentioning
confidence: 99%